A palladium-containing RHO zeolite nitrogen oxide adsorbent and preparation method thereof

By using powdered silicone to prepare high crystallinity RHO zeolite and load palladium elements, the problem that the prior art cannot efficiently control the nitrogen oxide emissions from diesel vehicles under low temperature conditions is solved, and excellent NOx storage capacity is maintained under high temperature hydrothermal conditions, meeting the practical application needs.

CN119034678BActive Publication Date: 2025-03-18NANKAI UNIV +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411299010.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-03-18
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The prior art cannot efficiently control the nitrogen oxides emitted by diesel vehicles under low temperature conditions, and it is known that the NOx adsorption capacity of PNA materials decreases after high temperature hydrothermal aging, which cannot meet the actual application needs.

Method used

High crystallinity RHO zeolites are prepared by using powdered silica gel as a source of silicon and loading palladium elements thereon, using specific preparation methods and treatment steps to ensure high dispersion and hydrothermal stability of palladium ions.

Benefits of technology

It achieves efficient adsorption and storage of nitrogen oxides under low temperature conditions, and maintains excellent NOx storage capacity and hydrothermal stability under high temperature hydrothermal conditions, meeting the actual needs of exhaust purification of diesel vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119034678B_ABST
    Figure CN119034678B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of nitrogen oxide gas purification, and in particular to a palladium-containing RHO zeolite nitrogen oxide adsorbent and a preparation method thereof. When the adsorbent is subjected to in-situ adsorption infrared analysis, the adsorbent has a peak value of 1840-1900cm ‑1 The infrared absorption peak intensity at 1780~1840cm ‑1 The ratio of the infrared absorption peak intensity at the position is greater than 0.9. The adsorbent contains at least silicon, aluminum and oxygen as skeleton atoms, wherein the molar ratio of silicon atoms to aluminum atoms is (2-50):1. The palladium in the adsorbent accounts for 0.1-5.0% of the mass of the RHO zeolite. The adsorbent not only has a high NO x It has high storage capacity and higher hydrothermal stability, and can be used as a PNA material to meet the actual needs of motor vehicle exhaust purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a palladium-containing RHO zeolite nitrogen oxide adsorbent and a preparation method thereof, belonging to the technical field of nitrogen oxide gas purification. Background Art

[0002] Nitrogen oxides (NO x ) emissions have become a serious concern of society. x Due to the impact on the environment and health, countries have formulated increasingly stringent emission regulations. As a mobile source, cars are the main contributor to traffic pollutant emissions, and diesel vehicles have NO x Emissions of NO in automobile emissions x So far, lean NO x Traps (LNT) and selective catalytic reduction (SCR) have been successfully developed and applied to NO x Emission control. It is worth noting that the LNT adsorbs and stores NO under lean combustion conditions. x , NO is released during rich combustion x , but its adsorption temperature is usually above 200℃. Selective catalytic reduction (SCR) technology using NH3 as a reductant is considered to be the most effective NO reduction technology for diesel vehicles. x Emission control technology, copper-based small-pore zeolite can show high NO in the range of 200℃ to 600℃ x However, during the cold start period of the vehicle (3-5 minutes when the temperature is below 180°C), neither of the above two technologies can effectively control NO x In addition, urea is difficult to decompose into NH3 at temperatures below 180°C, which sets technical limitations for the application of urea SCR process at low temperatures.

[0003] In order to solve the dilemma faced by the SCR system, the concept of CSC catalyst (Cold-Start Catalysts) was proposed in US Patent US8105559B2 to deal with the problem of low-temperature exhaust emissions from diesel engines. The CSC catalyst is based on a palladium-based catalyst supported by cerium oxide, which adsorbs and stores HCs and NO at low temperatures. x , and then at high temperature, the adsorbed HCs and NO x Released. But its existence NO x The low-temperature adsorption efficiency is low and cannot meet the application requirements of low-temperature nitrogen oxide storage. x adsorber, PNA) technology, using CHA type zeolite containing precious metal elements as NO xCompared with non-zeolite PNA materials, zeolite PNA materials containing noble metal elements show good NO adsorbent performance. x Compared with the palladium-containing CHA-type zeolite PNA material, patent WO2017 / 001828A1 discloses a palladium-containing LTL-type zeolite PNA material, which has higher NO x Release temperature. In addition, OFF-type zeolite (US20190217269A1), MAZ-type zeolite (WO2016135465A1), and STI-type zeolite (WO2019 / 186163A1) containing precious metals are also used as PNA adsorbent materials. Patent WO2022 / 243164 proposes a palladium-containing AFX-type zeolite PNA material, which not only has a high NO x storage capacity, and also has a high NO x Desorption temperature. Since the engine will emit high-temperature water vapor when it is running, the PNA material also needs to have high hydrothermal stability. However, the PNA materials disclosed in the prior art will cause NO desorption after high-temperature hydrothermal aging treatment. x The decrease in adsorption capacity cannot meet the needs of practical applications.

[0004] Related literature (Angew.Chem.Int.Ed.57(2018)16672–16677) believes that palladium ions are NO x Therefore, loading highly dispersed palladium ions in zeolite materials is the key to PNA materials. However, the dispersion of palladium ions is not only related to the preparation method, but also the stability of the zeolite structure is crucial to the dispersion of palladium ions and hydrothermal temperature. After hydrothermal treatment, the collapse of the zeolite structure will lead to the agglomeration of palladium ions, making PNA materials less responsive to NO. x The adsorption performance decreases. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a palladium-containing RHO zeolite nitrogen oxide adsorbent and a preparation method thereof. The adsorbent has high NO x It has high storage capacity and higher hydrothermal stability, and can be used as a PNA material to meet the actual needs of motor vehicle exhaust purification.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: The inventors have found through in-depth research that the selection of silicon source has an important influence on the synthesis of high-silicon and high-crystallinity RHO zeolite. If a nano-scale liquid silicon source (such as water-soluble silica sol) is used, the silicon source will be dissolved into sodium silicate during the synthesis process, which is not easy to form the double 8-membered ring structure of RHO zeolite, and the synthesized RHO zeolite often has a low crystallinity; if a powdered solid silicon source with particles below 50μm (such as fumed silica, white carbon black) is used, due to its extremely strong water absorption, the viscosity of the system increases sharply after adding the gel, and the initial gel fluidity is poor, which affects the mass transfer and heat transfer rate of the system, thereby causing the synthesized RHO zeolite to easily appear impure phases. When using powdered silica gel with a particle size of 50 to 300μm as the silicon source, the initial condensation viscosity is low, the mass transfer and heat transfer are sufficient, and the synthesized RHO molecular sieve has a high crystallinity and is not easy to produce impure phases. If a solid silicon source with a particle size of more than 300μm is used, it is difficult for RHO zeolite to crystallize because silica is not easy to dissolve during the reaction. The RHO zeolite synthesized with powdered silica gel with a particle size of 50 to 300 μm as the silicon source was loaded with palladium. When subjected to in-situ adsorption infrared analysis, the 1840-1900 cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at is greater than 0.9, and it has very excellent nitrogen oxide adsorption performance.

[0007] Furthermore, the adsorbent contains at least silicon, aluminum and oxygen as skeleton atoms, wherein the molar ratio of silicon atoms to aluminum atoms is (2-50):1.

[0008] Furthermore, the palladium in the adsorbent accounts for 0.1 to 5.0% of the mass of the RHO zeolite.

[0009] Furthermore, the adsorbent also contains one or more other elements selected from alkali metals, alkaline earth metals, rare earth metals and transition metals.

[0010] The present invention also discloses a method for preparing a palladium-containing RHO zeolite nitrogen oxide adsorbent, the preparation method comprising:

[0011] S1, mixing a mixture containing at least a silicon source, an aluminum source, an organic template and an inorganic base in water to obtain a primary gel;

[0012] S2, the primary gel is subjected to aging and hydrothermal synthesis reaction to obtain a reaction product;

[0013] S3, removing the organic template from the reaction product to obtain RHO zeolite;

[0014] S4, performing ion exchange on the RHO zeolite and ammonium salt, and calcining again;

[0015] S5. The calcined powder is uniformly mixed with a solution containing palladium, and then the powder is dehydrated and calcined again to obtain a palladium-containing RHO zeolite nitrogen oxide adsorbent.

[0016] Further, the silicon source is at least one of powdered silica gel, fumed silica, white carbon black, sodium silicate, silica sol, trimethylethoxysilane, and tetraethyl orthosilicate;

[0017] The aluminum source is at least one of sodium aluminate, aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum oxide, aluminum hydroxide, boehmite, aluminum chloride, aluminum silicate gel, and metallic aluminum;

[0018] The organic template is 18-crown ether-6;

[0019] The inorganic base is an alkali metal hydroxide.

[0020] Preferably, the silicon source is powdered silica gel, and further, the particle size of the powdered silica gel is 50 to 300 μm.

[0021] The aluminum source is sodium metaaluminate;

[0022] 18-crown ether-6 of the organic template;

[0023] The inorganic base is at least one of sodium hydroxide, potassium hydroxide, rubidium hydroxide and cesium hydroxide.

[0024] Furthermore, the solution containing the palladium element is at least one of a palladium nitrate solution, a palladium dichloride solution, a dichlorotetraamminepalladium solution, a palladium sulfate solution, and an ammonium tetrachloropalladate solution.

[0025] Furthermore, a catalytic reactor for nitrogen oxide purification is provided, wherein the purification device is provided with a palladium-containing RHO zeolite nitrogen oxide adsorbent as described herein, or a palladium-containing RHO zeolite nitrogen oxide adsorbent prepared according to the method described herein.

[0026] The beneficial effects of the present invention are:

[0027] In the preparation process of the palladium-containing RHO zeolite nitrogen oxide adsorbent of the present invention, powdered silica gel is used as a silicon source to prepare the initial gel, which can greatly reduce the viscosity of the gel system, so that the synthesized RHO zeolite has a higher crystallinity and is not easy to produce impurities, thereby making the final palladium-containing RHO zeolite nitrogen oxide adsorbent have a higher NOx storage capacity and hydrothermal stability.

[0028] In addition, compared with other palladium-containing small-pore zeolite nitrogen oxide adsorbents, the palladium-containing RHO zeolite nitrogen oxide adsorbent has a lower skeleton density and greater skeleton flexibility. When palladium is loaded, the palladium species are more easily dispersed into the zeolite pores, and there are more ionic palladium species. Therefore, the palladium-containing RHO zeolite has more NO x Effective adsorption sites, showing high efficiency of NO under aqueous conditions x Storage capacity, and under high temperature hydrothermal conditions, palladium species are not easily agglomerated in palladium-containing RHO zeolite, showing excellent hydrothermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 XRD pattern of zeolite A prepared in Example 1;

[0030] Figure 2 XRD pattern of the zeolite prepared in Comparative Example 5;

[0031] Figure 3 XRD pattern of the zeolite prepared in Comparative Example 6;

[0032] Figure 4 This is the NO in-situ adsorption infrared spectrum of the fresh PNA1A adsorbent prepared in Example 1 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0033] Figure 5 The infrared spectrum of NO in situ adsorption of the PNA1A aged adsorbent prepared in Example 1 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0034] Figure 6 This is the NO in-situ adsorption infrared spectrum of the fresh PNA1B adsorbent prepared in Example 2 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0035] Figure 7 The infrared spectrum of NO in situ adsorption of the PNA1B aged adsorbent prepared in Example 2 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0036] Figure 8The infrared spectrum of NO in situ adsorption of the fresh PNA1C adsorbent prepared in Example 3 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0037] Fig. 9 The infrared spectrum of NO in situ adsorption of the PNA1C aged adsorbent prepared in Example 3 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0038] Fig.10 The infrared spectrum of NO in situ adsorption of the fresh PNA2A adsorbent prepared in Comparative Example 1 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0039] Fig.11 The infrared spectrum of NO in situ adsorption of the PNA2A aged adsorbent prepared in Comparative Example 1 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0040] Fig.12 The infrared spectrum of NO in situ adsorption of the fresh PNA2B adsorbent prepared in Comparative Example 2 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0041] Fig.13 The infrared spectrum of NO in situ adsorption of the PNA2B aged adsorbent prepared in Comparative Example 2 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0042] Fig.14 The infrared spectrum of NO in situ adsorption of the fresh PNA3A adsorbent prepared in Comparative Example 3 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0043] Fig.15The infrared spectrum of NO in situ adsorption of the aged PNA3A adsorbent prepared in Comparative Example 3 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0044] Fig.16 The infrared spectrum of NO in situ adsorption of the fresh PNA3B adsorbent prepared in Comparative Example 4 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0045] Fig.17 The infrared spectrum of NO in situ adsorption of the aged PNA3B adsorbent prepared in Comparative Example 4 (h1 in the figure is 1840-1900 cm -1 The infrared absorption peak at h2 is 1780~1840cm -1 Infrared absorption peak at

[0046] Fig.18 NO for fresh agents of PNA1B, PNA2A and PNA3A x Curves of storage and release versus time;

[0047] Fig.19 NO is an aging agent for PNA1B, PNA2A and PNA3A x Storage and release versus time curve. DETAILED DESCRIPTION

[0048] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0049] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0050] 1. Zeolite

[0051] The zeolites mentioned in the present invention all refer to RHO zeolites specified by the International Zeolite Association (hereinafter referred to as IZA). Zeolites are usually regular mesh structures formed by the oxygen atoms at each vertex of the framework atom tetrahedron (such as SiO4 tetrahedron, AlO4 tetrahedron or PO4 tetrahedron, and the element atoms other than the oxygen element are usually referred to as non-oxygen atoms or T atoms) connected by sharing. For RHO zeolite, its structure can be determined by X-ray diffraction (XRD), and it is necessary to detect at least the interplanar spacing shown in Table 1 below, that is, if it has the interplanar spacing shown in Table 1 below, the zeolite can be RHO zeolite.

[0052] Table 1 Interplanar spacing

[0053]

[0054] 2. Synthesis of Zeolite

[0055] In the present disclosure, the synthesis method of zeolite adopts a hydrothermal synthesis method, in which raw materials and water are prepared into a primary gel, and then placed in a reaction container for a hydrothermal synthesis reaction, thereby synthesizing zeolite.

[0056] <Raw Materials>

[0057] The raw materials used in the production process of the RHO zeolite of the present invention mainly include a silicon source, an aluminum source, an organic template, an optional inorganic base and water. In addition, a component having a crystallization-promoting effect such as a seed crystal may also be added.

[0058] The silicon source may be at least one of powdered silica gel, fumed silica, white carbon, sodium silicate, silica sol, trimethylethoxysilane, and tetraethyl orthosilicate. The aluminum source may be at least one of sodium aluminate, aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum oxide, aluminum hydroxide, boehmite, aluminum chloride, aluminum silicate gel, and metallic aluminum.

[0059] The inorganic base can use at least one of alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide. In the manufacturing process of zeolite, as an alkali metal ion or an alkaline earth metal ion, at least one metal ion selected from the group consisting of lithium, sodium, potassium, rubidium, cesium, calcium, magnesium, strontium, and barium is preferably used for crystallization. By including these alkali metal ions, crystallization is easy and by-products (impurity crystals) are not easily generated. It should be noted that when calculating the molar ratio of the components in the gel, the corresponding oxide A2O of the inorganic base AOH is generally used to calculate the molar ratio.

[0060] <Preparation of aluminum source solution>

[0061] The aluminum source solution is prepared by dissolving the aluminum source in water. The aluminum source concentration of the aluminum source solution is preferably 5 to 50 wt %, particularly preferably 10 to 40 wt %, from the perspective of ease of gel preparation and production efficiency.

[0062] It should be noted that the aluminum source solution does not substantially contain silicon atoms. Here, "does not substantially contain" means that the silicon content in the aluminum source solution is 1% by weight or less, and preferably does not contain any silicon atoms.

[0063] <Preparation of Aqueous Gel>

[0064] An inorganic base is added to the aqueous solution to prepare an inorganic base solution. Then, the inorganic base solution, the silicon source solution, the aluminum source solution, and the organic template are uniformly mixed to prepare a gel-like mixture, which is an aqueous gel for the next step reaction.

[0065] In the process of preparing the gel-like mixture, the rate of adding each raw material solution is not limited and can be appropriately selected according to the use conditions.

[0066] It should be noted that if the silicon source is a liquid, it can be used as long as it is prepared as an aqueous dispersion of silicon dioxide with a concentration of about 5 to 60% by weight, such as silica gel. When preparing other liquids of raw materials containing silicon atoms, it is preferably prepared as an aqueous solution or aqueous dispersion with a concentration of the raw materials containing silicon atoms of 5% by weight or more, especially 10% by weight or more, and 60% by weight or less, especially 50% by weight or less.

[0067] Similar to the aluminum source solution, the silicon source liquid contains substantially no aluminum atoms. Here, "substantially no aluminum atoms" means that the aluminum content in the silicon source-containing liquid is 1 wt% or less, and preferably no aluminum atoms are contained.

[0068] The aqueous gel prepared as above can be subjected to hydrothermal synthesis immediately after preparation, but in order to obtain a zeolite with high crystallinity, it is preferably aged for a specific time under specified temperature conditions. The aging temperature is usually below 100°C, preferably below 80°C, and more preferably below 60°C. The lower limit is not particularly limited, and is usually above 0°C, and preferably above 10°C. The aging temperature can be constant or gradually changed during the aging. The aging time is not particularly limited, and is usually more than 2 hours, more than 3 hours, more than 5 hours, or more than 8 hours, and is usually less than 30 days, less than 10 days, less than 4 days, or less than 2 days.

[0069] <Hydrothermal Synthesis>

[0070] The hydrothermal synthesis is carried out as follows: the aqueous gel prepared as above is placed in a pressure-resistant container, and the temperature is maintained under autogenous pressure or gas pressure to a degree that does not hinder crystallization, under stirring conditions, or under conditions where the container is rotated or shaken, or in a static state, thereby carrying out hydrothermal synthesis.

[0071] The reaction temperature during hydrothermal synthesis is usually 90° C. or more, preferably 120° C. or more, usually 300° C. or less, preferably 250° C. or less, and more preferably 200° C. or less. The reaction time is not particularly limited, but is usually 2 hours or more, 6 hours or more, or 12 hours or more, and usually 30 days or less, 10 days or less, or 7 days or less. The reaction temperature may be constant or gradually changed during the reaction.

[0072] After the above hydrothermal synthesis, the RHO zeolite as a product is separated from the hydrothermal synthesis reaction liquid. The obtained RHO zeolite (hereinafter referred to as "RHO zeolite containing template etc.") contains one or more of an organic template and an alkali metal in its pores. The method for separating the zeolite containing template etc. from the hydrothermal synthesis reaction liquid is not particularly limited, and generally, methods such as filtration, decantation or direct drying can be cited.

[0073] <Impurity Removal, Calcination and Ion Exchange>

[0074] In order to remove the organic template and alkali metal ions used in the manufacturing process, the RHO zeolite containing the template and the like separated and recovered from the hydrothermal synthesis reaction solution can be washed with water and dried (for example, dried at 80°C to 100°C for 1 to 12 hours) as needed, and then the organic template and alkali metal ions can be subsequently removed.

[0075] The removal treatment of the template and / or alkali metal can be carried out by liquid phase treatment using an acidic solution, a chemical solution containing a template decomposition component, an ion exchange treatment using a resin, etc., a thermal decomposition treatment, or a combination of these treatments. Generally, the organic matter (template, etc.) contained can be removed by calcining at a temperature of 300°C to 800°C in air or an inert gas atmosphere containing oxygen, or in an inert gas atmosphere, or by extraction using an organic solvent such as an ethanol aqueous solution.

[0076] From the perspective of production, it is preferred to remove the template and the like by calcination. In this case, the calcination temperature is preferably 400°C or higher, more preferably 450°C or higher, and further preferably 500°C or higher, and preferably 900°C or lower, and more preferably 850°C or lower.

[0077] The temperature is preferably 800° C. or lower, more preferably 800° C. or lower. As the inert gas, a gas such as nitrogen may be used, and an inert component such as water vapor (for example, 5% to 10% water vapor) may be added to the gas.

[0078] In addition, the ion exchange capacity of zeolite can also be used to convert the alkali metal part into H type or NH4 type, and the method can adopt well-known technology. It can be treated with ammonium salts such as NH4NO3, NH4Cl, (NH4)2SO4 or acidic solutions such as hydrochloric acid at room temperature to 100°C and then washed with water. NH4 type zeolite can be further converted into H type zeolite by roasting. As an inactive gas, a gas such as nitrogen can be used, and an inactive component such as water vapor (for example, 5% to 10% water vapor) can also be added to the gas.

[0079] The palladium metal can be added to the RHO framework zeolite by any known means, for example, the palladium-containing compound can be loaded onto the zeolite by impregnation, adsorption, ion exchange, precipitation, spray drying, etc. The exchanged zeolite is then dried (for example, dried at 80°C to 100°C for 1 to 12 hours) and calcined. As the inactive gas, a gas such as nitrogen can be used, and an inactive component such as water vapor (for example, 5% to 10% water vapor) can also be added to the gas.

[0080] The roasting equipment of the present disclosure is not particularly limited, and common industrial kilns such as muffle furnaces, tunnel kilns or rotary kilns can be used. From the perspective of the convenience of continuous production, a rotary kiln is preferably used.

[0081] Method of using palladium-containing RHO zeolite nitrogen oxide adsorbent:

[0082] The palladium-containing RHO zeolite nitrogen oxide adsorbent can be used directly in powder form, or it can be mixed with an adhesive to prepare a mixture containing zeolite and then used. The adhesive used can usually be an inorganic adhesive such as silica, alumina, zirconium oxide, or a polysiloxane-based organic adhesive. Polysiloxanes refer to oligomers or polymers having a polysiloxane bond in the main chain, and also include substances in which a part of the substituents of the main chain of the polysiloxane bond is hydrolyzed to form hydroxyl groups. The amount of adhesive used is not particularly limited, and can usually be 1 to 20% by weight, and 2 to 15% by weight in consideration of the strength during molding.

[0083] The palladium-containing RHO zeolite nitrogen oxide adsorbent of the present invention or the mixture containing zeolite can also be used after granulation or molding. The method of granulation or molding is not particularly limited, and various well-known methods can be used. Usually, the zeolite mixture is shaped and used as a molded body. The shape of the molded body can be various. For example, when the zeolite of the present disclosure is used as a catalyst for purifying nitrogen oxides in exhaust gas from mobile sources (vehicles, ships, etc.), the method of applying the zeolite can be a coating method or a molding method to shape the zeolite into a honeycomb adsorbent. The coating method is usually to mix the zeolite with an inorganic adhesive such as silica, alumina or zirconia to make a slurry, and then apply it to the surface of a honeycomb made of an inorganic material such as cordierite, and then dry and burn it. The molding method is usually to mix the zeolite with an inorganic adhesive such as silica, alumina or inorganic fibers such as alumina fibers and glass fibers, and shape it into a honeycomb by extrusion or compression, and then dry and burn it.

[0084] Nitrogen oxides and their purification

[0085] The palladium-containing RHO-type zeolite nitrogen oxide adsorbent of the present invention purifies nitrogen oxides by contacting the exhaust gas containing nitrogen oxides. The nitrogen oxides to be purified include nitrogen monoxide, nitrogen dioxide, nitrous oxide, etc. The palladium-containing RHO-type zeolite nitrogen oxide adsorbent of the present invention can effectively adsorb nitrogen oxides at low temperatures, and release the adsorbed nitrogen oxides when the temperature rises to a certain level. When the zeolite of the present disclosure is used as an adsorbent, it can purify nitrogen oxides contained in various exhaust gases discharged from diesel vehicles, gasoline vehicles, stationary power generation ships, agricultural machinery, construction machinery, two-wheeled or three-wheeled motor vehicles, various gasoline and diesel engines for aircraft, boilers, gas turbines, etc.

[0086] A palladium-containing RHO zeolite nitrogen oxide adsorbent, when the adsorbent is subjected to in-situ adsorption infrared analysis, 1840-1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensities at is greater than 0.9.

[0087] More specifically, the adsorbent contains at least silicon, aluminum and oxygen as skeleton atoms, wherein the molar ratio of silicon atoms to aluminum atoms is (2-50):1.

[0088] More specifically, the palladium in the adsorbent accounts for 0.1 to 5.0% of the mass of the RHO zeolite.

[0089] More specifically, the palladium-containing RHO zeolite nitrogen oxide adsorbent may further contain one or more other elements selected from alkali metals, alkaline earth metals, rare earth metals and transition metals.

[0090] A method for preparing a palladium-containing RHO zeolite nitrogen oxide adsorbent, the preparation method comprising:

[0091] S1, mixing a mixture containing at least a silicon source, an aluminum source, an organic template and an inorganic base in water to obtain a primary gel;

[0092] S2, the primary gel is subjected to aging and hydrothermal synthesis reaction to obtain a reaction product;

[0093] S3, calcining the reaction product and removing the organic template to obtain RHO zeolite;

[0094] S4, performing ion exchange on the RHO zeolite and ammonium salt, and calcining again;

[0095] S5. The calcined powder is uniformly mixed with a solution containing palladium, and then the powder is dehydrated and calcined again to obtain a palladium-containing RHO zeolite nitrogen oxide adsorbent.

[0096] The silicon source is at least one of powdered silica gel, fumed silica, white carbon black, sodium silicate, silica sol, trimethylethoxysilane, and tetraethyl orthosilicate;

[0097] The aluminum source is at least one of sodium aluminate, aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum oxide, aluminum hydroxide, boehmite, aluminum chloride, aluminum silicate gel, and metallic aluminum;

[0098] The organic template is 18-crown ether-6;

[0099] The inorganic base is an alkali metal hydroxide;

[0100] Preferably, the silicon source is powdered silica gel, and the particle size of the powdered silica gel is 50 to 300 μm;

[0101] Specifically, in the primary gel, the molar ratio of SiO2, Al2O3, R, A2O, and H2O corresponding to the silicon source, aluminum source, organic template, inorganic base, and water is (5-100):1:(5-20):(2-20):(100-1000).

[0102] Specifically, the solution containing the palladium element is at least one of a palladium nitrate solution, a palladium dichloride solution, a dichlorotetraamminepalladium solution, a palladium sulfate solution, and an ammonium tetrachloropalladate solution.

[0103] Specifically, in step S2, the aging temperature condition is 10-60° C., and the aging time is 8-48 hours;

[0104] The hydrothermal synthesis reaction temperature is 120-200° C., and the hydrothermal synthesis reaction time is 1-7 days;

[0105] In step S4, the calcination temperature is 300-700° C., and the calcination time is 2-72 hours;

[0106] In step S5, the calcination temperature is 300-800° C., and the calcination time is 2-72 hours. In actual production or experiments, appropriate process parameters can be selected within the above conditions according to actual conditions, but are not limited to the conditions.

[0107] Specifically, a catalytic reactor for purifying nitrogen oxides is provided, wherein the purification device is provided with a palladium-containing RHO zeolite nitrogen oxide adsorbent as described herein, or a palladium-containing RHO zeolite nitrogen oxide adsorbent prepared according to the method described herein.

[0108] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0109] The performance measurement method involved in the embodiment is:

[0110] (1) Powder XRD determination

[0111] The X-ray diffraction measuring instrument is Rigaku MiniFlex600, the detection light source is Cu Kα, the tube voltage is 40kV, the tube current is 40mA, the detection angle range is 3-55°, and the scanning speed is 8° / min. The physical structure of the synthesized zeolite is determined by X-ray diffraction: the ground sample powder is added into the square hole on the glass plate, and then the glass plate is inserted into the axis position of the goniometer. Under the irradiation of the Cu Kα light source, the probe rotates at a speed of 2θ / min.

[0112] (2) Sample NO x Adsorption-desorption test

[0113] The prepared catalyst was stamped, crushed and granulated. The granulated zeolite (0.7 g) was filled into a fixed bed flow-through reactor tube at normal pressure. A gas containing the composition in Table 2 was circulated over the catalyst layer, and the catalyst layer was heated at the same time. The adsorption temperature was 100°C and the adsorption time was 30 min. After the adsorption was completed, programmed temperature desorption was performed in this atmosphere at a heating rate of 10°C / min to 500°C. An FTIR analyzer was used to measure the concentrations of NO, NO2, NH3, N2O, H2O and O2 at the reactor outlet.

[0114] Table 2 Composition of gas flowing over the catalyst layer

[0115]

[0116]

[0117] (3) NO in situ adsorption infrared (FT-IR) analysis

[0118] Place the pressed zeolite flakes in an in-situ transmission cell, introduce a 50 mL / min mixed gas (10% volume fraction of O2, 90% volume fraction of N2), heat the sample to 500°C and treat it for 0.5 h before cooling it down to 100°C. Collect infrared spectra at this temperature as background spectra. Introduce 200 ppm NO gas (10% volume fraction of O2, 2.5% volume fraction of H2O, balance gas is N2, and the total gas flow rate is still 50 mL / min), and record the infrared spectrum data after 30 minutes of saturated adsorption of zeolite. Since the positions of the infrared vibration peaks of the palladium ions and palladium oxides loaded on the zeolite after adsorbing NO are different, the palladium species loaded on the zeolite can be qualitatively and quantitatively analyzed based on the infrared absorption peak intensities at different positions. When the palladium-containing zeolite described in this article is subjected to in-situ NO adsorption infrared analysis, the 1840-1900 cm -1 The infrared absorption peak intensity at 1780-1840cm -1 The infrared absorption peak intensity is at 2000~2200cm -1 The peak is taken as the baseline, and the highest point of the peak in the corresponding interval is taken as the vertex. The height of the absorption peak is calculated as the intensity of the absorption peak. -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensities at is greater than 0.9. The palladium-containing RHO zeolite with the above characteristics has excellent nitrogen oxide adsorption performance, is less affected by water in the ambient atmosphere, and has high hydrothermal stability.

[0119] (4) Hydrothermal aging test

[0120] 2.0 g of zeolite sample was placed in a tubular furnace, with an air flow rate of 300 mL / min and a water vapor content of 10%. The hydrothermal treatment temperature was 850° C. and the hydrothermal treatment time was 12 h.

[0121] Example 1

[0122] The preparation steps of a palladium-containing RHO zeolite nitrogen oxide adsorbent (0.5%wt palladium-containing RHO zeolite) are as follows:

[0123] 42.4 g of 18-crown ether-6 (manufactured by Shanghai Sigma-Aldrich Co., Ltd.) was dissolved in 28.0 g of deionized water, and then 5.8 g of sodium hydroxide (manufactured by Tianjin Fengchuan Chemical Reagent Co., Ltd.) and 16.0 g of cesium hydroxide (cesium hydroxide concentration: 50 wt%, manufactured by Shanghai Sigma-Aldrich Co., Ltd.) were added in sequence to dissolve into a mixed solution, and then the mixed solution was stirred at 70°C for 3 hours to obtain a crown ether complex A solution. 0.64 g of sodium aluminate (alumina content: 45 wt%; sodium oxide content: 38 wt%; manufactured by Tianjin Fengchuan Chemical Reagent Co., Ltd.) and 0.2 g of sodium fluoride (manufactured by Tianjin Fengchuan Chemical Reagent Co., Ltd.) were weighed in a polytetrafluoroethylene bottle and dissolved in 2.8 g of deionized water. Subsequently, 8.45 g of silica sol (silicon dioxide concentration: 40 mass%, Shanghai Sigma-Aldrich Co., Ltd.), 9 g of crown ether complex A solution, and 10 g of deionized water were added in sequence to form a mixed gel. After the gel was stirred evenly, the sealed polytetrafluoroethylene bottle was transferred to a stainless steel autoclave and placed in a rotary blast oven at 140°C for 6 days. After being taken out, the solid was filtered and washed with water, and then placed in a 100°C blast oven for overnight drying. The final powder sample was named RHO seed.

[0124] Dissolve 3.2g of sodium aluminate (alumina content: 45 wt%, sodium oxide content: 38 wt%, manufactured by Tianjin Fengchuan Chemical Reagent Co., Ltd.) in 89g of water, add 21.9g of powdered silica gel (silicon dioxide content: 85 mass%, particle size: 50-300μm, manufactured by Qingdao Kangyexin), then add 45.0g of crown ether complex A solution and 0.8g of RHO seed crystals, and stir evenly to obtain an aqueous gel. After stirring and aging at room temperature (25°C) for 12 hours, the aqueous gel is placed in a temperature and pressure resistant container, and after hydrothermal synthesis at 140°C for 96 hours, the reaction liquid is cooled. The powder obtained is filtered and recovered and dried overnight at 100°C to obtain zeolite A1 containing the template. The XRD measurement results of zeolite A1 are as follows. Figure 1 As shown, it is a RHO type zeolite. The molar ratio of SiO2 to Al2O3 of the zeolite tested by ICP is 16.3. Zeolite A1 was calcined at 560°C in air for 6 hours to remove the organic template, thereby obtaining zeolite A2.

[0125] 5.4 g of ammonium chloride (Tianjin Fengchuan Chemical Reagent Co., Ltd.) was dissolved in 100 g of water, and then 10 g of zeolite A2 was added to form a slurry, and the ion exchange was carried out at 80°C for 2 hours. The reaction solution was cooled, filtered and recovered, and the obtained powder was dried at 100°C for 2 hours. After repeating the above steps for 5 times of ion exchange, the obtained powder was calcined in air at 550°C for 6 hours to obtain zeolite A.

[0126] 0.0675 g of ammonium tetrachloropalladate (palladium content: 36.7 wt%, Shaanxi Ruike New Materials Co., Ltd.) was dissolved in 4.5 g of deionized water, and the ammonium tetrachloropalladate solution was added to 5 g of zeolite A by an equal volume impregnation method. After drying at 100°C, the sample was calcined in air at 550°C for 4 hours to obtain adsorbent PNA1A. In situ NO adsorption infrared analysis of adsorbent PNA1A was performed as follows: Figure 4 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 1.03 is 1.03. The nitrogen oxide adsorption performance of PNA1A is shown in Table 3.

[0127] In situ NO adsorption infrared analysis of PNA1A aged samples Figure 5 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at is 1.37. The nitrogen oxide adsorption performance of the PNA1A aged sample is shown in Table 3.

[0128] Example 2

[0129] The preparation steps of a palladium-containing RHO zeolite nitrogen oxide adsorbent (1.0%wt palladium-containing RHO zeolite) are as follows:

[0130] 0.135 g of ammonium tetrachloropalladate (palladium content: 36.7 wt%, Shaanxi Ruike New Materials Co., Ltd.) was dissolved in 4.5 g of deionized water, and the ammonium tetrachloropalladate solution was added to 5 g of zeolite A by an equal volume impregnation method. After drying at 100°C, the sample was calcined in air at 550°C for 4 hours to obtain adsorbent PNA1B. In situ NO adsorption infrared analysis of adsorbent PNA1B was performed as follows: Figure 6 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 1.27 is 1.27. The Pd loading of PNA1B is 1.0%. The nitrogen oxide adsorption performance of PNA1B is shown in Table 3 and Fig.18 shown.

[0131] In situ NO adsorption infrared analysis of PNA1B aged samples Figure 7 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 0.95 is 0.95. The nitrogen oxide adsorption performance of the PNA1B aged sample is shown in Table 3 and Fig.19 shown.

[0132] Example 3

[0133] The preparation steps of a palladium-containing RHO zeolite nitrogen oxide adsorbent (2.0%wt palladium-containing RHO zeolite) are as follows:

[0134] 0.27 g of ammonium tetrachloropalladate (palladium content: 36.7 wt%, Shaanxi Ruike New Materials Co., Ltd.) was dissolved in 4.5 g of deionized water, and the ammonium tetrachloropalladate solution was added to 5 g of zeolite A by an equal volume impregnation method. After drying at 100°C, the sample was calcined in air at 550°C for 4 hours to obtain adsorbent PNA1C. In situ NO adsorption infrared analysis of adsorbent PNA1C was performed as follows: Figure 8 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 1.13 is 1.13. The Pd loading of PNA1C is 2.0%. The nitrogen oxide adsorption performance of PNA1C is shown in Table 3.

[0135] In situ NO adsorption infrared analysis of PNA1C aged samples Fig. 9 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at is 1.18. The nitrogen oxide adsorption performance of the PNA1C aged sample is shown in Table 3.

[0136] Comparative Example 1

[0137] PNA2A: 1%wt of CHA zeolite containing palladium

[0138] 0.135 g of ammonium tetrachloropalladate (palladium content: 36.7 wt%, Shaanxi Ruike New Materials Co., Ltd.) was dissolved in 4.6 g of deionized water, and the ammonium tetrachloropalladate solution was added to 5 g of CHA type zeolite (the molar ratio of SiO2 to Al2O3 was 16.0, manufactured by Zhuoran Environmental Protection Technology Co., Ltd.) by an equal volume impregnation method. After drying at 100°C, the sample was calcined in air at 550°C for 4 hours to obtain adsorbent PNA2A. In situ NO adsorption infrared analysis of adsorbent PNA2A was performed as follows Fig.10 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 0.60. The Pd loading of PNA2A is 1.0%. The nitrogen oxide adsorption performance of PNA2A is shown in Table 3 and Fig.18 shown.

[0139] In situ NO adsorption infrared analysis of PNA2A aged samples Fig.11 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 0.77 is 0.77. The nitrogen oxide adsorption performance of the PNA2A aged sample is shown in Table 3 and Fig.19 shown.

[0140] Comparative Example 2

[0141] PNA2B: 2%wt of CHA zeolite containing palladium

[0142] 0.27 g of ammonium tetrachloropalladate (palladium content: 36.7 wt%, Shaanxi Ruike New Materials Co., Ltd.) was dissolved in 4.6 g of deionized water, and the ammonium tetrachloropalladate solution was added to 5 g of CHA type zeolite (the molar ratio of SiO2 to Al2O3 was 16.0, manufactured by Zhuoran Environmental Protection Technology Co., Ltd.) by an equal volume impregnation method. After drying at 100°C, the sample was calcined in air at 550°C for 4 hours to obtain adsorbent PNA2B. Infrared analysis of NO in situ adsorption of adsorbent PNA2B was performed as follows Fig.12 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 0.80 is 0.80. The Pd loading of PNA2B is 2.0%. The nitrogen oxide adsorption performance of PNA2B is shown in Table 3.

[0143] In situ NO adsorption infrared analysis of PNA2B aged samples Fig.13 As shown, 1840~1900cm -1 The infrared absorption peak intensity of NO at 1780-1840cm -1 The ratio of the infrared absorption peak intensity at is 0.78. The nitrogen oxide adsorption performance of the PNA2B aged sample is shown in Table 3.

[0144] Comparative Example 3

[0145] PNA3A: 1%wt palladium-containing AEI zeolite

[0146] 0.135 g of ammonium tetrachloropalladate (palladium content: 36.7 wt%, Shaanxi Ruike New Materials Co., Ltd.) was dissolved in 4.0 g of deionized water, and the ammonium tetrachloropalladate solution was added to 5 g of AEI zeolite (molar ratio of SiO2 to Al2O3 is 16.7, manufactured by Zhuoran Environmental Protection Technology Co., Ltd.) by equal volume impregnation method. After drying at 100°C, the sample was calcined in air at 550°C for 4 hours to obtain adsorbent PNA3A. In situ NO adsorption infrared analysis of adsorbent PNA3A was performed as follows Fig.14 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 0.51 is 0.51. The Pd loading of PNA3A is 1.0%. The nitrogen oxide adsorption performance of PNA3A is shown in Table 3 and Fig.16 shown.

[0147] In situ NO adsorption infrared analysis of PNA3A aged samples Fig.15 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 0.68 is 0.68. The nitrogen oxide adsorption performance of the PNA3A aged sample is shown in Table 3 and Fig.19 shown.

[0148] Comparative Example 4

[0149] PNA3B: 2%wt palladium-containing AEI zeolite

[0150] 0.27 g of ammonium tetrachloropalladate (palladium content: 36.7 wt%, Shaanxi Ruike New Materials Co., Ltd.) was dissolved in 4.0 g of deionized water, and the ammonium tetrachloropalladate solution was added to 5 g of AEI zeolite (molar ratio of SiO2 to Al2O3 is 16.7, manufactured by Zhuoran Environmental Protection Technology Co., Ltd.) by an equal volume impregnation method. After drying at 100°C, the sample was calcined in air at 550°C for 4 hours to obtain adsorbent PNA3B. In situ NO adsorption infrared analysis of adsorbent PNA3B was performed as follows Fig.16 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at 0.87 is 0.87. The Pd loading of PNA3A is 2.0%. The nitrogen oxide adsorption performance of PNA3B is shown in Table 3.

[0151] In situ NO adsorption infrared analysis of PNA3B aged samples Fig.17 As shown, 1840~1900cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at is 0.63. The nitrogen oxide adsorption performance of the PNA3B aged sample is shown in Table 3.

[0152] Comparative Example 5

[0153] RHO zeolite was prepared by the same method as in Example 1, except that the powdered silica gel was replaced with silica sol (silicon dioxide concentration: 40 mass %, Shanghai Sigma-Aldrich Co., Ltd.). The XRD measurement results of the synthetic zeolite are shown in Figure 2 shown.

[0154] Comparative Example 6

[0155] RHO zeolite was prepared by the same method as in Example 1, except that the powdered silica gel was replaced with fumed silica (Shanghai Simon Chemical Co., Ltd.). The XRD results of the synthetic zeolite are shown in Figure 3 shown.

[0156] Table 3 Adsorption performance data

[0157]

[0158] The (h1 / h2) in the table is the 1840-1900 cm-1 in the sample NO in situ adsorption infrared spectrum. -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensities at .

[0159] It can be seen from the experimental data of Example 1 and Comparative Example 5 that if the silicon source is replaced with silica sol, the crystallinity of the synthesized RHO zeolite will be significantly lower. This is because the silica sol particles are nanometer-sized and can be easily completely dissolved into sodium silicate during the synthesis process, affecting the growth of crystals.

[0160] It can be seen from the experimental data of Example 1 and Comparative Example 6 that if the silicon source is replaced with fumed silica, obvious MOR impurities will appear in the synthesized RHO zeolite, because fumed silica is a solid flocculent small particle with extremely strong water absorption. After being added, the gel basically no longer has fluidity, which seriously affects the mass transfer and heat transfer rate of the synthesis process, resulting in local unevenness of the gel and the generation of impurities.

[0161] The results in Table 3 show that the palladium-containing RHO zeolite nitrogen oxide adsorbent prepared by the preparation method of the present invention in Examples 1-3 has an infrared absorption rate of 1840-1900 cm-1 for NO in situ adsorption. -1 A strong infrared absorption peak is shown at the point where the palladium ions in this special state are the dominant form when the RHO zeolite of the present invention is loaded with palladium. The palladium ions in this form are not easily affected by water atmosphere and can maintain a high nitrogen oxide adsorption capacity under water conditions. The palladium ions have a high hydrothermal stability and even have a higher nitrogen oxide adsorption capacity after hydrothermal aging.

[0162] In addition, it can be seen from the experimental data of Comparative Examples 1-4 and Examples 1-3 that the palladium-containing RHO zeolite nitrogen oxide adsorbent of the present invention is much higher than the palladium-containing CHA and palladium-containing AEI zeolites synthesized in the prior art in terms of hydrothermal stability, low-temperature NOx adsorption amount and adsorption efficiency of loaded Pd.

[0163] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0164] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A palladium-containing RHO zeolite nitrogen oxide adsorbent, characterized in that: When the adsorbent is subjected to in-situ adsorption infrared analysis, 1840-1900 cm -1 The infrared absorption peak intensity at 1780~1840cm -1 The ratio of the infrared absorption peak intensity at is greater than 0.9; the adsorbent is prepared using powdered silica gel as a silicon source, and the particle size of the powdered silica gel is 50-300 μm.

2. The palladium-containing RHO zeolite nitrogen oxide adsorbent according to claim 1, characterized in that: The adsorbent contains at least silicon, aluminum and oxygen as skeleton atoms, wherein the molar ratio of silicon atoms to aluminum atoms is (2-50):

1.

3. The palladium-containing RHO zeolite nitrogen oxide adsorbent according to claim 1, characterized in that: The palladium in the adsorbent accounts for 0.1-5.0% of the mass of the RHO zeolite.

4. The palladium-containing RHO zeolite nitrogen oxide adsorbent according to claim 1, characterized in that: The adsorbent further comprises one or more other elements selected from alkali metals, alkaline earth metals, rare earth metals and transition metals.

5. A method for preparing a palladium-containing RHO zeolite nitrogen oxide adsorbent according to any one of claims 1 to 4, characterized in that: The preparation method is: S1, mixing a mixture containing at least a silicon source, an aluminum source, an organic template and an inorganic base in water to obtain a primary gel; the silicon source is powdered silica gel, and the particle size of the powdered silica gel is 50-300 μm; S2, obtaining a reaction product after the primary gel is subjected to aging and hydrothermal synthesis reaction; S3, removing the organic template from the reaction product to obtain RHO zeolite; S4, performing ion exchange on the RHO zeolite and ammonium salt, and calcining again; S5. The calcined powder is uniformly mixed with a solution containing palladium, and then the powder is dehydrated and calcined again to obtain a palladium-containing RHO zeolite nitrogen oxide adsorbent.

6. The method for preparing a palladium-containing RHO zeolite nitrogen oxide adsorbent according to claim 5, characterized in that: The aluminum source is at least one of sodium aluminate, aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum oxide, aluminum hydroxide, boehmite, aluminum chloride, aluminum silicate gel, and metallic aluminum; The organic template is 18-crown ether-6; The inorganic base is an alkali metal hydroxide.

7. The method for preparing a palladium-containing RHO zeolite nitrogen oxide adsorbent according to claim 5, characterized in that: The solution containing the palladium element is at least one of a palladium nitrate solution, a palladium dichloride solution, a dichlorotetraamminepalladium solution, a palladium sulfate solution, and an ammonium tetrachloropalladate solution.

8. A gas purification device, wherein: The purification device is provided with a palladium-containing RHO zeolite nitrogen oxide adsorbent according to any one of claims 1-4, or a palladium-containing RHO zeolite nitrogen oxide adsorbent prepared by the method according to any one of claims 5-7.

Citation Information

Patent Citations

  • Passive NOX adsorber

    US20150158019A1

  • Passive NOX adsorber

    US20190217269A1

  • Thermally regenerable nitric oxide adsorbent

    US8105559B2

  • PASSIVE NOx ADSORBER

    WO2016135465A1

  • PASSIVE NO x ADSORBER

    WO2017001828A1